Structural gender-based violence as a master frame - Bonu Rosenkranz, Giada; Barone, Anastasia (Frontiers in Political Science, 2025)
This paper examines how feminist movements in Italy have reframed gender-based violence as a structural issue, leading to the creation of structural gender-based violence as a master frame. Drawing on frame analysis and interviews with feminist activists, the study explores how the Non Una Di Meno (NUDM) movement challenged prevailing media narratives that framed violence as an individual or exceptional phenomenon. Instead, NUDM diagnosed patriarchy as a systemic cause of violence, linking it to intersecting oppressions such as capitalism, racism, and institutional inequality. By emphasizing the structural nature of violence, the movement broadened its scope to address issues like labor rights, reproductive freedom, and migration, creating resonance through accessible, emotionally impactful messages. The study highlights how diagnostic, motivational, and prognostic frames contributed to the emergence of structural gender-based violence as a master frame, which unified diverse struggles and enhanced the mobilizing potency of feminist movements. This master frame facilitated large-scale participation and transnational solidarity, linking local struggles to global contexts. By analyzing NUDM's framing process, the paper underscores the role of feminist movements in reshaping societal understandings of violence and advancing systemic change, offering both theoretical and empirical contributions to the study of social movements and framing theory.